Estimating Peak Shaving Capacity Demand of Gas-Fired Power in China From a Regional Coordination Perspective - Zhang, Shuquan; Wang, Ye; Zhao, Xu; Duan, Xuqiang; Luo, Dongkun (Frontiers in Energy Research, 2022)
Facing the carbon neutralization goal and renewable energy development, it is of great significance to promote the construction of gas-fired power generation for power peak shaving. From the perspective of regional coordination (corresponding to three scenarios), this paper systematically calculates the power peak shaving demand and the demand for gas-fired power generation capacity in regions of China, by using Mathematical Programming and Shapley value. Compared with the existing research, this paper may make theoretical contributions in the following aspects, including studying more spatial scopes and time scales of peak shaving, analyzing the complete system of "coal power - renewable energy - gas power", and applying cooperative game model to peak shaving issue. We find that, firstly, compared with the scenario of independent peak shaving in single province (Scenario 1), the peak shaving demands of load and renewable energy are greatly reduced in the scenarios of areal coordination (Scenario 2) and national coordination (Scenario 3), especially renewable energy; secondly, abandonment of 110,766 MWh of renewable energy power occurring in Scenario 2 is avoided in Scenario 3. Compared with Scenario 2, the final peak shaving demands of 7 areas in China are simultaneously reduced in Scenario 3. The largest reduction rate is 14% from East China; thirdly, with deep peak shaving restricted by certain constraints, gas power generation for start-stop peak shaving is inevitable. Compared with Scenario 2, national coordination (Scenario 3) can eliminate 120,714 MW of start-stop peak shaving demand (SS-PSD); finally, flexibility retrofit of existing facilities can further significantly curtail SS-PSD. Based on the above research results, some recommendations are put forward, including developing areal coordination and national coordination mechanisms for peak shaving, clarifying allocation plan of SS-PSD based on the fairness principle (i.e., Shapley value) as soon as possible, encouraging East China, Central China and North China to take the lead in establishing trading markets of SS-PSD, giving priority to meeting the most urgent and economic peak shaving demand, and establishing coordination mechanism between new and old units for flexibility retrofit.